MANAGERIAL REPORTING SYSTEM FOR TOP MANAGEMENT IN THE FINANCIAL SYSTEM XYZ - Dwi Windu Irianto; Ir. Setidjo Budiutomo (Jurnal Sistem Informasi, 1994)
This study aims to be able to choose the package software programs that support the reporting for top management. The results of this study indicate that the package of software programs that most support in managerial reporting is Lotus, which is supported by the Add-in Wysiwyg programs.